Nursing Students' Level of Knowledge About HIV/AIDS - Athiutama, Ari; Erman, Imelda; Febriani, Indra (PT.Mantaya Idea Batara, 2024)
HIV/AIDS causes health problems in the world, resulting in death. HIV/AIDS sufferers require long-term treatment from health services. Nursing students are part of health services. This research is quantitative research with a descriptive approach. The sample was determined using a total sampling technique and obtained 230 respondents. Data collection used the HIV Knowledge Questionnaire 45 (HIV-KQ-45). Data were analyzed univariately to see the frequency distribution of the research variables. The data was analyzed univariately to observe the frequency distribution of the research variables. The research results showed that most nursing students' knowledge about HIV/AIDS was in the sufficient category (66.5%) and the least in the good category (14.8%). From the results obtained, it was concluded that the majority of nursing students' knowledge about HIV/AIDS was in the sufficient category and the minority was in the good category. This shows that students' knowledge about HIV/AIDS is still inadequate. It is necessary to prepare prospective nurses starting during education to avoid a lack of knowledge in the hope of improving services to HIV/AIDS sufferers as much as possible in the future.